2020
DOI: 10.1093/jscr/rjaa163
|View full text |Cite
|
Sign up to set email alerts
|

Parotid adenocarcinoma metastasis to the breast: a case report

Abstract: Abstract Metastatic salivary gland tumors are rare clinical entities of the head and neck. Parotid gland carcinoma with distant metastases heralds a poor prognosis with a median survival of 4.3–7.3 months. The lungs, long bones, liver and brain are the most common sites of metastasis for parotid gland cancer, along with a few reported cases describing metastasis to the ileum, spleen and iliac crest. We present the first case to our knowledge of parotid adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Brandon et al, reported a rare case of metastasis of Parotid Adenocarcinoma to breast. 10 The patient underwent wide local excision of the lesion with clear tumour margins. Due to cutaneous involvement of the lesion, the skin had to be reconstructed by harvesting the Pectoralis Major Myocutaneous Muscle Flap (PMMC) for esthetic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Brandon et al, reported a rare case of metastasis of Parotid Adenocarcinoma to breast. 10 The patient underwent wide local excision of the lesion with clear tumour margins. Due to cutaneous involvement of the lesion, the skin had to be reconstructed by harvesting the Pectoralis Major Myocutaneous Muscle Flap (PMMC) for esthetic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Primary salivary gland malignancies (SGMs) account for only 5% of all head and neck cancers, with the World Health Organization (WHO) describing 11 benign and 22 malignant subtypes of salivary gland tumors [ 1 ]. Carcinoma ex pleomorphic adenoma (CXPA) constitutes about 12% of all SGMs, with the majority of cases arising from the parotid gland (67%) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, poorly differentiated adenocarcinoma and undifferentiated carcinoma are the most frequently encountered malignant components of CXPA with squamous cell carcinoma (SCC) being a rare finding [ 3 , 4 ]. Metastatic SGMs are an uncommon finding with only 20% of parotid gland malignancies showing metastatic potential [ 1 ]. According to Ali et al, lungs account for 49%, bones for 40%, and the brain for 7% of the total metastasis reported in a study.…”
Section: Introductionmentioning
confidence: 99%
“…14 months later, a nodule was found in the patient's right lung⁵. Additionally, research bySmith et al (2020) presented parotid gland metastatic adenocarcinoma to the breast. The patient underwent left radical parothyrodectomy and underwent radiotherapy.…”
mentioning
confidence: 98%